Protein structure and dynamics in the era of integrative structural biology - Grandori, Rita (Frontiers in Biophysics, 2023)
Proteins carry out their biological activity as dynamic structures and populate in solution or in biological membranes structural distributions with different degrees of heterogeneity. The central challenge in structural biology is to capture protein structural dynamics under equilibrium or kinetic conditions shifting from single, static pictures to movies of conformational ensembles. Ideally, this task should be pursued both in vitro and in vivo, under the influence of the native environment. The last decade has seen a tremendous development of biophysical methods for the investigation of protein structure and dynamics. However, each method has specific limitations and no single approach offers such a complex level of description. Nonetheless, the combination of experimental and computational complementary methods is opening promising new avenues. Also the ambition of implementing structural studies on an omic scale is becoming more and more realistic. In spite of still major limitations, integrative structural biology is bringing dynamics into structural proteomics with exciting perspectives for basic and applied sciences.